Report on the conference of leading personalities of Eastern Nigeria origin (Enugu : The Government Printer, 1964)
This is a report on the conference of leaders of Eastern Nigeria origin held in Enugu, Eastern Nigeria from 13-14 December 1963. If focuses on efforts to industrialise the region
lje 11/05/2018
Ref
Keywords: Industrialisation; Nigeria